Скрининг элементного состава плодов древесных и кустарниковых растений из коллекций Донецкого ботанического сада НАН Украины - Остапко, И.Н. (Промышленная ботаника, 2004)
Element composition of fruits of arboreal and shrub plants of 42 species from 8 families and 19 genera during fruitage phase has been determined at the Donetsk Botanical Gardens of the National Academy of Sciences of Ukraine within 1992-2003. The species with maximal contents of both separate vital elements and their various combinations are distinguished. Some exceedings of maximum permissible concentration of Fe, Zn, Cr, Pb, Cd are fixed. Therefore, gathering of raw material of the investigated species as sources of microelements is recommended to be carried out far from industrial enterprises.